Prospectively assessed neurodevelopmental outcomes in studies of anaesthetic neurotoxicity in children: a systematic review and meta-analysis. (February 2021) - Ing, Caleb; Jackson, William M.; Zaccariello, Michael J.; Goldberg, Terry E.; McCann, Mary-Ellen; Grobler, Anneke; Davidson, Andrew; Sun, Lena; Li, Guohua; Warner, David O.
Abstract: Background: Whether exposure to a single general anaesthetic (GA) in early childhood causes long-term neurodevelopmental problems remains unclear. Methods: PubMed/MEDLINE, Embase, CINAHL, Web of Science, and the Cochrane Library were searched from inception to October 2019. Studies evaluating neurodevelopmental outcomes and prospectively enrolling children exposed to a single GA procedure compared with unexposed children were identified. Outcomes common to at least three studies were evaluated using random-effects meta-analyses. Results: Full-scale intelligence quotient (FSIQ); the parentally reported Child Behavior Checklist (CBCL) total, externalising, and internalising problems scores; and Behavior Rating Inventory of Executive Function (BRIEF) scores were assessed. Of 1644 children identified, 841 who had a single exposure to GA were evaluated. The CBCL problem scores were significantly higher (i.e. worse) in exposed children: mean score difference (CBCL total: 2.3 [95% confidence interval CI: 1.0–3.7], P =0.001; CBCL externalising: 1.9 [95% CI: 0.7–3.1], P =0.003; and CBCL internalising problems: 2.2 [95% CI: 0.9–3.5], P =0.001). Differences in BRIEF were not significant after multiple comparison adjustment. Full-scale intelligence quotient was not affected by GA exposure. Secondary analyses evaluating the risk of these scores exceeding predetermined clinical thresholds found that GA exposure was associated with increased risk of CBCL internalising behavioural deficit (risk ratio [RR]: 1.47; 95% CI: 1.08–2.02; P =0.016) and impaired BRIEF executive function (RR: 1.68; 95% CI: 1.23–2.30; P =0.001). Conclusions: Combining results of studies utilising prospectively collected outcomes showed that a single GA exposure was associated with statistically significant increases in parent reports of behavioural problems with no difference in general intelligence.